2016
DOI: 10.4995/wrs.2016.3665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant extracts and essential oils as feed supplements on quality and microbial traits of rabbit meat

Abstract: The effects of dietary supplementation with onion, cranberry and strawberry extracts and essentials oils on meat quality were analysed. Five groups of 48 Grimaud female weaned rabbits received the supplemented or the control ration; the experimental unit was a cage of 6 rabbits. Each experimental diet contained 10 ppm of added active ingredients. Rabbits were fed with the experimental diets for 4 wk before determining slaughter and carcass traits and determining the pH at 1 and 24 h post mortem (pHu) of the Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
21
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 41 publications
9
21
1
1
Order By: Relevance
“…However, in rabbits supplemented with chia (Meineri et al, 2010), the observed LL pH (5.65) was lower compared to that observed in T2 group (6.06) of the present study. The pH values obtained by Kone et al (2016) for LL and BF meat from rabbits supplemented with plant extracts and essential oils were similar to those observed for the T2 group in the present study, but L* and a* values were lower. Finally, meat composition results in the current study were similar to those obtained by Rotolo et al (2013), Dalle Zotte et al (2015, Cardinali et al (2015), and Méndez-Zamora et al (2016) evaluating natural additives.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, in rabbits supplemented with chia (Meineri et al, 2010), the observed LL pH (5.65) was lower compared to that observed in T2 group (6.06) of the present study. The pH values obtained by Kone et al (2016) for LL and BF meat from rabbits supplemented with plant extracts and essential oils were similar to those observed for the T2 group in the present study, but L* and a* values were lower. Finally, meat composition results in the current study were similar to those obtained by Rotolo et al (2013), Dalle Zotte et al (2015, Cardinali et al (2015), and Méndez-Zamora et al (2016) evaluating natural additives.…”
Section: Discussionsupporting
confidence: 88%
“…These findings suggest that hydrolysed sorghum treatment does not affect carcass traits and meat composition. On the other hand, the CL of LL for the T2 treatment was higher than that for Pannon Large and Hungarian Giant rabbit genotypes fed commercial diets (Dalle Zotte et al, 2015), but was similar to those obtained with Grimaud rabbits (Kone et al, 2016). The WHC values obtained by Ariño et al (2006) were similar to those observed in the T2 group.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, lipid oxidation adversely impacts the meat quality as it causes the formation of some toxic compounds and malondialdehyde (MDA). The latter has been exhibited to contrarily influence human's health (Koné et al, 2016;Cardinali et al, 2015). Natural feed addition derived from plants, for example, the essential oils have been suggested as alternative feed supplements in animal production for improving growth performance and the meat quality characteristics (Bento et al, 2013;Simitzis & Deligeorgis, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…El empleo de diversos aceites esenciales de especias y hierbas para alimentar animales tiene la finalidad de mejorar la estabilidad oxidativa de la carne (Kone et al, 2016), disminuir sus cargas microbianas (Soultos et al, 2009) y mejorar su productividad (Cardinali et al, 2015). En el caso de los aceites esenciales de ruda, se han caracterizado sus compuestos volátiles, Franca y Nascimento (2015), encontraron que los principales compuestos volátiles son 2-nonanona y 2-undecanona; reportan actividad antimicrobiana contra bacterias Gram positivas y negativas.…”
Section: Introductionunclassified